2019
DOI: 10.3390/en12040756
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Planning of Integrated Energy Systems for Offshore Oil Extraction and Processing Platforms

Abstract: With the introduction of new technologies, such as waste heat recovery units (WHRU), associated gas utilization, the energy flow coupling relationship is further deepened within the energy system of the offshore oil and gas production platform. Besides, the energy system is closely linked with the oil and gas production system, and a closed-loop relationship between energy flow and material flow can be revealed. Uncertainties of energy supply and production process may lead to system-wide fluctuations, which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Ardal, et al, has mentioned the power demand in the range of [40][41][42][43][44][45]. Zhang, et al, studied four offshore platforms, each with different activities (extraction, processing, support and maintenance, and storage) gives a peak power demand of approximately 44 MW [21]. Another difference is that the platforms may operate individually or work together to form a single and central power platform, providing power to the others.…”
Section: B Energy Demand For An Offshore Oil Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ardal, et al, has mentioned the power demand in the range of [40][41][42][43][44][45]. Zhang, et al, studied four offshore platforms, each with different activities (extraction, processing, support and maintenance, and storage) gives a peak power demand of approximately 44 MW [21]. Another difference is that the platforms may operate individually or work together to form a single and central power platform, providing power to the others.…”
Section: B Energy Demand For An Offshore Oil Platformsmentioning
confidence: 99%
“…Oliveira-Pinto, et al state that, 50 % of the energy supply was to be fulfilled by natural gas while diesel fuels supply the other 50 % [2]. On the other hand, Zhang, et al found co-firing turbines at the platforms which can run on natural gas, diesel, or hydrogen [21]. The energy demand for some of the offshore oil platforms is shown in Table I, where the energy requirements vary from 10 MW to 45 MW depending on the well sizes.…”
Section: B Energy Demand For An Offshore Oil Platformsmentioning
confidence: 99%
“…Therefore, the structure of OMIES can be equivalent to biological membrane FMM. In addition, the energy-material flow analysis starts from the energy flow model, the material flow model, and the energy-material flow feedback model, and analyzes the material-energy transfer and transformation process in OMIES [24]. Risk can be further expressed by the system's material-energy transfer and transformation, so OMIES energy flow and material flow are considered as risk carriers.…”
Section: The Risk Fluid Mosaic Model Of Omiesmentioning
confidence: 99%
“…Since σ 1 and σ 2, Eq2 and Eq3 are also in the feedback part, their elements represent the same, but have different values. Each element in the substance and energy conversion matrix of the above model is the calculated value of the conversion relationship of the corresponding part [24], and each element of the risk flow matrix is the value of the operating state of the corresponding equipment under risk. The value is between 0 and 2, 0 means no output of the device, 1 means normal output, greater than 1 means overrun of the device, and a value between 0 ∼ 1 means derated operation of the device, the specific value is determined by the operating characteristics of the device.…”
Section: The Risk Fluid Mosaic Model Of Omiesmentioning
confidence: 99%
“…However, this introduces the problem of coupling the intermittent behavior of the wind power production with the high criticality and reliability requirements of the supplied loads. The critical point from a technical perspective is that the uncertainties associated to the energy supply and production processes can lead to system-wide power fluctuations, which can, in their turn, threaten the stability and reliability of the platform's operations [6], [7]. Facing this problem requires flexible solutions that may include advanced energy resources scheduling [8], efficient coordination of the various subsystems [9] and integrating an energy storage system in the platform's grid.…”
Section: Introductionmentioning
confidence: 99%